Analysis of maternal mortality in a tertiary care hospital of a metropolitan city - Mulla, Shakila; Gupta, Pankaj Kumar; Ansari, Shakeel (Indian Journal of Community Health, 2015)
Introduction: In developing countries like India, maternal mortality ratio is still very high. Current study is an attempt to analyze maternal mortality and its determinants in a tertiary care hospital where highest quality of medical care is provided. Methods: It was a retrospective study. Five years data from January 2004 to December 2008 was reviewed from medical record department of tertiary care hospital in Mumbai. Fisher’s exact test was applied; Odds ratio and 95% confidence interval were calculated. SPSS Version 16.0 was used to analyse data. Result: Maternal mortality ratio was 68.4 per one lakh live births. Major cause of maternal mortality observed was haemorrhage. Multigravida, Age above 30 years and lack of antenatal check-up were significantly associated with higher risk of maternal mortality. Conclusion: Maternal mortality is still high even in a tertiary care centre as compared to MMR (Maternal Mortality Ratio) in developed countries. Timely monitoring/ management during antenatal and intra-natal period would substantially reduce maternal mortality.